KAJIAN DAYA SERAP VEGETASI TERHADAP EMISI GAS CO2 YANG DIHASILKAN KENDARAAN BERMOTOR DALAM MITIGASI BENCANA EKOLOGI DI KOTA BANDA ACEH - Abdullah .; Nizam Ismail; Budi Aulia (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Banda Aceh is a city with an area of 61.36 km2. Transportation activities result in increased resulting in air pollution which resulted in ecological disaster. Increased carbon dioxide must be offset by the addition of enough greening crops. This study was conducted to assess the absorption of vegetation on carbon dioxide emissions generated by motorvehicles in Banda Aceh City that is green line on the Five road with samples taken five working days starting at 06.30-18.30. Traffic data at peak hours is used to calculate the production of carbon dioxide emissions generated and the area of vegetation cover on the research sites measured from 2015 satellite images using ArcGIS 10.1. Based on the results of the study, the accumulated carbon dioxide emissions of 182.578.8 kg / hr with the absorption of vegetation of 14,374.8 kg / hr or 7.87%. To absorb the emissions required additional vegetation cover area of 107.88 ha or 1.76%. Banda Aceh City Government can make several mitigation efforts to balance the concentration of carbon dioxide in the air, namely: Improvement of public transportation; Establishment and implementation of 3 in 1 system; Maintaining Green Open Space; Improving Greening Activities.